2000
DOI: 10.4049/jimmunol.164.2.1103
|View full text |Cite
|
Sign up to set email alerts
|

Myelin-Associated Oligodendrocytic Basic Protein: Identification of an Encephalitogenic Epitope and Association with Multiple Sclerosis

Abstract: Myelin-associated oligodendrocytic basic protein (MOBP) is an abundant myelin constituent expressed exclusively by oligodendrocytes, the myelin-forming cells of the CNS. We report that MOBP causes experimental allergic encephalomyelitis and is associated with multiple sclerosis. First, we note that purified recombinant MOBP inoculated into SJL/J mice produces CNS disease. Tests of overlapping peptides spanning the murine MOBP molecule map the encephalitogenic site to amino acids 37–60. MOBP-induced experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 54 publications
(50 reference statements)
2
59
1
Order By: Relevance
“…Our results expanded previous data (Holz et al, 2000;Kaye et al, 2000) showing that MOBP should also be considered as a target of CD4 + T cell responses in MS. The MS patients analyzed here had heterogeneous MHC class II types (see Table 1); yet PBMC from all of them reacted to at least one MOBP peptide at one or more time points.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results expanded previous data (Holz et al, 2000;Kaye et al, 2000) showing that MOBP should also be considered as a target of CD4 + T cell responses in MS. The MS patients analyzed here had heterogeneous MHC class II types (see Table 1); yet PBMC from all of them reacted to at least one MOBP peptide at one or more time points.…”
Section: Discussionsupporting
confidence: 90%
“…MOBP peptides were synthesized at TSRI peptide core facility by standard FMOC synthesis chemistry and were >95% pure as judged by HPLC and by mass spectrometry. Earlier report showed that these selected overlapping MOBP peptides induced a lymphoproliferative response of MS patients' PBMC (Holz et al, 2000). Recombinant human IL-2 (50 U/ml) (Roche, Nutley, NJ) was added 5 days after the beginning of the incubation.…”
Section: Isolation and Stimulation Of Human Peripheral Mono-nuclear Cmentioning
confidence: 99%
See 2 more Smart Citations
“…When SJL/J mice are immunized with an equimolar mixture of nonacylated encephalitogenic peptides PLP 139 -151 and PLP 178 -191 , responses to both peptides are equally strong (10,23). By contrast, if EAE is induced by immunization of SJL/J mice with whole spinal cord homogenate, which contains many potential autoantigens (4,10,(43)(44)(45), including PLP with covalently attached fatty acids, the dominant immune response is to PLP 139 -151 (46). Additionally, if EAE is induced in SJL/J mice with another autoantigen such as MBP, or if these mice are infected with Theiler's murine encephalomyelitis virus and allowed to recover, PLP 139 -151 is the first new epitope against which autoreactivity subsequently develops (47,48).…”
Section: Discussionmentioning
confidence: 99%